Effect of Irrigation on Growth of Three Tree Species in Indian Arid Zone - Bala, N; Singh, G; Bohra, N K (Annals of Arid Zone, 2016)
A trial was initiated in July 1995 to study the performance of Acacianilotica, Eucalyptus cal7laldulensis and Dalbergia sissoo under two irrigation levels(WI = 30 mm and W2 = 45 mm) and three frequencies (1] = 0.2, 12 = 0.3 and13 = 0.4) on a loamy sand soil. Irrigation schedule was maintained on the basisof IW/CPE ratio (irrigation water/cumulative pan evaporation). Average height ofall three species was best (P